A systematic in-vivo toxicity evaluation of nanophosphor particles via zebrafish models - Jang, Gun Hyuk; Hwang, Mintai P.; Kim, Su Yeon; Jang, Ho Seong; Lee, Kwan Hyi (ELSEVIER SCI LTD, 2014)
Lanthanide ion-doped nanophosphors are an emerging group of nanomaterials with excellent optical properties, and have been suggested as alternatives to quantum dots. In this letter, we determine the in-vitro and in-vivo toxicity of beta-NaYF4:Ce,Tb nanophosphors using Capan-1 cells and embryonic zebrafish, respectively. In particular, we are the first to report on the in-vivo toxicity of beta-phase nanophosphors and examine phenotypic developmental abnormalities (growth retardation, heart deformity, and bent tail), apoptotic cell death, and changes in heart function due to the nanophosphors. This study suggests the use of beta-NaYE4:Ce,Tb nanophosphors as alternatives for QDs in a wide variety of biomedical imaging applications. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: NANOPARTICLES; SIZE